An Enhanced Rate-Based Emission Trading Program for NOx: The Dutch Model - Anne M. Sholtz; Bill VanAmburg; Verne K. Wochnick (The Scientific World Journal)
Since 1997 government and industry in The Netherlands have been engaged in intensive policy discussions on how to design an emission trading program that would satisfy the Government’s policy objectives within the national and international regulatory framework and accommodate industry’s need for a flexible and cost-effective approach. Early on in the discussion the most promising solution was a rate-based approach, which dynamically allocated saleable emission credits based on a performance standard rate and actual energy used by facilities. All industrial facilities above a threshold of 20 MWth would be judged on their ability to meet this performance rate. Those “cleaner” than the standard can sell excess credits to others with an allocation that is less than their actual NOX emission. With some changes in law, such a design could be made to fit well into the national and EU legislative framework while at the same time uniquely meeting industry’s requirement of flexibility toward economic growth and facility expansion. (An analysis of the legislative changes required will be given in a separate paper by Chris Dekkers.) However, the environmental outcome of such a system is not as certain as under an absolute emission cap. At the request of the Netherlands Ministry of Housing, Spatial Planning and the Environment (VROM), Automated Credit Exchange (ACE), in close cooperation with the working group of government and industry representatives introduced a number of features into the Dutch NOX program allowing full exploitation of market mechanisms while allowing intermediate adjustments in the performance standard rates. The design is geared toward meeting environmental targets without jeopardizing the trading market the program intends to create. The paper discusses the genesis of the two-tier credit system ACE helped to design, explains the differences between primary (fixed) and secondary (variable) credits, and outlines how the Dutch system is expected to function once implemented in 2004. The paper also discusses the market trading simulation held in early 2001 to assess and test the trading program, and reviews also the current status of the market program development.